Sustainable Sport Center Design in Kumantan Village - Rijal, Muhammad; Husaini, Muhd. Arief Al; Kuswoyo, Indra; Hidayat, Wahyu; Mashuri, Mashuri; Dewi, Oriana Paramita (Indonesian Journal of Advanced Social Works, 2024)
Kumantan Village, Kampar Regency, requires adequate sports facilities. The design of this Sport Center aims to provide eco-friendly and sustainable facilities to support community sports activities such as football, volleyball, and futsal. The Neo Vernacular architectural approach is applied to create a design that aligns with the local identity. A SWOT analysis reveals significant potential to improve public health, sports achievements, and open economic opportunities. The design includes a stadium, jogging track, multipurpose hall, and supporting facilities, which are expected to become a hub for sports and social activities in the village.